2003
DOI: 10.1039/b307263k
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the percentage volume particle size distribution of powdered microcrystalline cellulose using reflectance near-infrared spectroscopyElectronic supplementary information (ESI) available: Particle size and spectral data. See http://www.rsc.org/suppdata/an/b3/b307263k/

Abstract: This is the first reported method for determining the percentage volume particle size distribution of a powder (microcrystalline cellulose) by near-infrared (NIR) reflectance spectroscopy. A total of 113 samples of powdered microcrystalline cellulose were used from six different commercially available grades, with different moisture contents (range: 0.9-4.8% m/m). NIR reflectance measurements of these samples were made in narrow soda glass vials. Reference particle size data for the samples were acquired by la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Utilizing near-infrared (NIR) spectroscopy as a tool to assess particle sizes of powdered materials in general and carbonate minerals in particular spans many fields of scientific endeavour including planetary exploration [1][2][3][4]. It is generally accepted that NIR bands in the 4000-6000cm -1 (2.5-1.67μm) region stem from overtones and combinations of the different internal modes of the [CO 3 2-] anion although comprehensive assignments of NIR bands are incomplete [1,2,5,6] and, there is a paucity of documented experimental accounts of the NIR spectral response from carbonate mineral powders as a function of grain size.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing near-infrared (NIR) spectroscopy as a tool to assess particle sizes of powdered materials in general and carbonate minerals in particular spans many fields of scientific endeavour including planetary exploration [1][2][3][4]. It is generally accepted that NIR bands in the 4000-6000cm -1 (2.5-1.67μm) region stem from overtones and combinations of the different internal modes of the [CO 3 2-] anion although comprehensive assignments of NIR bands are incomplete [1,2,5,6] and, there is a paucity of documented experimental accounts of the NIR spectral response from carbonate mineral powders as a function of grain size.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that absorbance values gave lower root mean square errors of prediction (RMSEPs) and bias than f(R). O'Neil et al 5 also reported that, for a particle size distribution of microcrystalline cellulose, absorbance values gave the best performance and the lowest RMSEP when compared with other pre-processing techniques.…”
Section: Granule Characterisationmentioning
confidence: 98%
“…13 Further, near-infrared spectroscopy has recently been applied to the particle-size determination by using a simultaneous chemoinfometric calibration method, which showed its usefulness. 14,15 No paper, however, was reported concerning attempts of the particle-size determination by using the ATR technique in the infrared region other than ours. In the present work, theoretical treatments of this particle-size-determination method by applying the ATR technique were stated, and based on these, the ATR-spectral intensities were calculated as functions of some variables, such as the sample amount on the reflection surface and the particle size for various choices of the experimental parameters.…”
Section: Introductionmentioning
confidence: 99%